Tuning Immobilized Enzyme Features by Combining Solid-Phase Physicochemical Modification and Mineralization - José R. Guimarães; Diego Carballares; Javier Rocha-Martin; Paulo W. Tardioli; Roberto Fernandez-Lafuente (International Journal of Molecular Sciences, 2022)
Lipase B from Candida antarctica (CALB) and lipase from Thermomyces lanuginosus (TLL) were immobilized on octyl agarose. Then, the biocatalysts were chemically modified using glutaraldehyde, trinitrobenzenesulfonic acid or ethylenediamine and carbodiimide, or physically coated with ionic polymers, such as polyethylenimine (PEI) and dextran sulfate. These produced alterations of the enzyme activities have, in most cases, negative effects with some substrates and positive with other ones (e.g., amination of immobilized TLL increases the activity versus p-nitro phenyl butyrate (p-NPB), reduces the activity with R-methyl mandate by half and maintains the activity with S-isomer). The modification with PEI increased the biocatalyst activity 8-fold versus R-methyl mandelate. Enzyme stability was also modified, usually showing an improvement (e.g., the modification of immobilized TLL with PEI or glutaraldehyde enabled to maintain more than 70% of the initial activity, while the unmodified enzyme maintained less than 50%). The immobilized enzymes were also mineralized by using phosphate metals (Zn2+, Co2+, Cu2+, Ni2+ or Mg2+), and this affected also the enzyme activity, specificity (e.g., immobilized TLL increased its activity after zinc mineralization versus triacetin, while decreased its activity versus all the other assayed substrates) and stability (e.g., the same modification increase the residual stability from almost 0 to more than 60%). Depending on the enzyme, a metal could be positively, neutrally or negatively affected for a specific feature. Finally, we analyzed if the chemical modification could, somehow, tune the effects of the mineralization. Effectively, the same mineralization could have very different effects on the same immobilized enzyme if it was previously submitted to different physicochemical modifications. The same mineralization could present different effects on the enzyme activity, specificity or stability, depending on the previous modification performed on the enzyme, showing that these ...